Civil Engineering and Urban Planning 2012 2012
DOI: 10.1061/9780784412435.010
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Planning and Design for Gymnasiums in Universities in the New Period

Abstract: With the development of the society, the education and the construction of the campus in recent years, the designing of Gymnasium in Universities is facing many new problems, which has aroused public attention. The planning and design for gymnasium in universities are integrated and studied as a whole. People start to explore the possible direction of development from its own characteristics, so that the original intention of the design are implemented and reflected in the project construction and utilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recently, many scholars have proposed various approaches to predict potential links in bipartite networks [24][25][26][27][28][29]. Benchettara et al [24] introduced new indicators of network structure characteristics to measure the appearance possibility of potential links and applied classical supervised machine learning approaches to modelling prediction problems.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many scholars have proposed various approaches to predict potential links in bipartite networks [24][25][26][27][28][29]. Benchettara et al [24] introduced new indicators of network structure characteristics to measure the appearance possibility of potential links and applied classical supervised machine learning approaches to modelling prediction problems.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Zhang et al [28] identified false and missing links in bipartite networks by employing the processes of local diffusion to evaluate the internal similarity. Chang et al [29] predicted potential links in Wikipedia which is a characteristic bipartite network by making use of a strengthened supervised machine learning method.…”
Section: Theoretical Backgroundmentioning
confidence: 99%